Investigation into the impacts of procurement systems on the performance of construction projects in East Malaysia - Odhigu, F.; Yahya, Azhar; Rani, N.; Shaikh, Junaid (Inderscience, 2012)
This research investigated the impacts of procurement systems on the performance of construction projects in East Malaysia. Construction project outcome is measured in terms of time, cost and quality achieved. Project clients demand the best value for their money and they want their projects to be completed on time, within budgeted cost and at appropriate quality or specification. The sample in this research consists of 58 participants that work in a construction companies/industry. About 90 questionnaires were distributed, 69 were successfully returned and 58 were fully completed. The sample comprises project clients/owners, project managers, consultants and construction workers. The aim of using project clients, project managers, consultants and construction workers from different companies is because they work under different circumstances. The researchers distributed questionnaires randomly among the participants in different construction companies. The key findings showed that traditional procurement system (TPS) benefits cost and quality but at the expense of time. In other words, TPS has positive impacts on project objectives of cost and quality and negative impact on project time. Whereas, design and build procurement system showed that project objectives of cost and time are positive with negative impact on project quality.